Perencanaan Pembangkit Listrik Tenaga Surya Sistem Off-Grid di Desa Bungku Kecamatan Bajubang Kabupaten Batanghari Jambi - Abdul Manab; Iyan Torang H; Andre Rabiula; Hendi Matalata (Journal of Electrical Power Control and Automation (JEPCA), 2022)
This study aims to plan a solar power plant with an off grid system that will be used for electricity needs in Hamlet Kunangan Jaya 2 RT.28 which is one of the Hamllet in Bungku Village. Bungku Village is included in the 3T area, which is left behind, foremost, and outermost.Hamle Kunangan Jaya 2 RT.28have not enjoyed electricity from PLN due to difficult access and far from urban areas.The research was conducted with a descriptive research method. The selection of this type of method is used on the basis of the consideration that the nature of the research describes a plan carried out to meet the electricity needs of public facilities. Studies field were carried out to determine the electricity needs of public facilities: Mosques, Polides, and Elementary Schools, find out the number of panels needed, measure solar radiation and measure the area of the building. Calculation of electricity requirements is carried out in order to find out how much electricity is needed in public facilities, carry out design plans and calculate a budget plan to describe the planned installation. The results of solar data measurement for Optimal Global Irradiation in Bungku Village are 4,549kWh/m2 per day, the required amount of solar cell power is 6,000WP, three 40A Solar Charger Controllers, 2,800Ah batteries and 8000Watt Inverters. The total load required for mosques, polides, and elementary schools is 25,126Wh. The total RAB for PLTS development using an off-grid system requires a cost of IDR 138,647,000.